Culture, climate, and landscape shape the savanna and wetland mosaic of the Bolivian Amazon - Whitney, Bronwen S.; Walker, John H.; Duncan, Neil A.; Loughlin, Nicholas J. D. (Frontiers in Water, 2024)
Environmental archeology of the Amazon has conventionally focused on terrestrial spaces, investigating crop domestication and production, agroforestry and anthropogenic soils. Aquatic environments, however, have been given less attention by archeologists and paleoenvironmental scientists alike. The Llanos de Mojos, a 135,000 km2 basin of the Amazon and mosaic landscape of savannas, wetlands and forests, has long been recognized for its archeological record. A variety of anthropogenic earthworks across the region show significant landscape modifications from Pre-Columbian times used for transportation, resource production and control of floodwaters. Here, we investigate the use and management of wetlands, and their interaction in the wider Mojos mosaic landscape, by integrating extensive archeological, paleoenvironmental and GIS datasets. We demonstrate that past human modifications of the landscape enabled the creation of complex wetland-terrestrial system of resource production, in which wetlands were managed, complementary to terrestrial crop production and agroforestry. Across short distances (40 km), land use strategies were heterogeneous despite being connected in time and space. Additionally, mixed wetland-terrestrial resource production was relatively stable during periods of lower rainfall from 1200–1500 CE, implying that this strategy provided flexibility under conditions of variable climate. The wetlands of the Llanos de Mojos are the result of millennia of human intervention and recognition of this deep heritage is required to make informed management and conservation decisions to ensure the future of this culturally and biologically diverse region.